Clinical features of gingivostomatitis due to primary infection of herpes simplex virus in children - Huang, Chen-Wei (BMC Infect Dis, 2020)
BACKGROUND: Primary herpetic gingivostomatitis (PHGS) in children, though usually self-limited, might mimic bacterial and enteroviral pharyngitis clinically. We conducted a study to define the clinical features of PHGS in children. METHODS: Between January 2012 and December 2016, 282 inpatients aged less than 19 years with cell culture-confirmed herpes simplex virus (HSV) infection in a medical center were identified from the virologic laboratory logbook. Clinical data were retrospectively collected. RESULTS: Among the 282 inpatients, 185 cases were considered as PHGS and were included for analysis. Fever was present in 99.5%. The mean duration of fever was 5.11 days (±2.24) with the longest being 17 days. Common oral manifestations included oral ulcers (84.3%), which equally resided in the anterior and posterior part of the oral cavity (65.4% vs. 63.2%), gum swelling and/or bleeding (67.6%), and exudate coated tonsils (16.8%). Leukocytosis (WBC count > 15,000/uL(3)) was noted in 52 patients (28.1%) and a serum C-reactive protein level > 40 mg/L in 55 patients (29.7%). Fixty-five patients (35%) were diagnosed with PHGS on admission and were significantly more likely to have ulcers over the anterior oral cavity (76.1% vs. 26.7%) and gum swelling/bleeding (76.2% vs. 7.5%, p-value all < 0.001) on admission and were significantly less likely to receive antibiotic treatment (16.9 vs. 36.7%, p-value < 0.01) than others. Forty-six patients (25%) undiagnosed as PHGS on discharge were significantly more likely to have exudate coated on the tonsils, to receive antibiotic treatment and significantly less likely to have gum swelling/bleeding and oral ulcers (all p-values < 0.01). CONCLUSIONS: Meticulously identifying specific oral manifestations of gum swelling/bleeding and ulcers over the anterior oral cavity in children can help making the diagnosis of PHGS earlier and subsequently reduce unnecessary prescription of antibiotics.